Determination of toxic diethylene glycol in toothpastes in Dar es Salaam by high performance thin layer chromatography and colorimetric methods - Mahugija, John Andrew Marco (Tanzania Journal of Science, 2018)
The aim of this study was to determine the presence and the levels of diethylene glycol (DEG) in toothpaste products commonly used in Dar es Salaam. Forty five samples of different brands of imported and locally manufactured toothpastes were collected and processed prior to analysis. High performance thin layer chromatography (HPTLC) method was used for the qualitative detection of diethylene glycol in the toothpastes. In quantitative analysis, a colorimetric method that involved ultraviolet–visible (UV-Vis) spectrophotometric measurements of absorbances of prepared coloured samples and standards was used. DEG was found in 37.8% of the tested samples. The concentrations of the DEG detected in the samples varied from 0.106 to 7.71 mg/g. The results indicated that 88.2% of the samples found with DEG were obtained from imported toothpastes and 11.8% of the samples found with DEG were from local pharmaceutical industries. The findings indicate public health risks because, according to the WHO standards, toothpastes should have no traces of DEG as it is toxic. There is a need for regular checking of the composition of both imported and locally manufactured toothpastes by the regulatory authorities. Keywords: Diethylene glycol, Toothpaste, TLC, UV-Vis Spectrophotometry, Tanzania